Psychosocial wellbeing and risky health behaviors among Syrian adolescent refugees in South Beirut: a study using the HEEADSSS interviewing framework - Rizk, Youssef; Hoteit, Reem; Khater, Beatrice; Naous, Jihane (Frontiers in Psychology, 2023)
Purpose Adolescent refugees are at risk of mental health disorders and underdiagnosed risky behaviors. Limited research exists in the Middle East and North Africa. This study aims to assess psychosocial wellbeing and risk-taking behaviors among adolescent refugees displaced to South Beirut following a standardized framework. Methods A cross-sectional study using face-to-face confidential HEEADSSS (Home, Education/Employment, Eating, Activities, Drugs, Sexuality, Safety and Suicide/Depression) interviews was conducted among 52 Syrian adolescent refugees, between the ages of 14 and 21, in a health center in South Beirut. Results The mean age of the interviewees was 17.04 ± 1.77 years, with a male predominance 34 (65.4%). Five (9.6%) were married, 38 (73.1%) were not attending school 27 (52.9%) lived in a place with a crowding index ≥3.5 and 21 (40.4%) were working. Risky health concerns or behaviors detected included no activities or exercise 38 (73.1%), eating one to two meals per day 39 (75%) and smoking 22 (42.3%). Eleven (21.2%) have been ever offered drugs and 22 (42.3%) believed they should carry a weapon for protection. Twenty one out of 32 (65.7%) had major depressive disorders and 33 (63.5%) screened positive for behavioral problems. Exposure to home verbal or physical violence, male gender, smoking, and employment were associated with high scoring in behavioral problems. Smoking and ever been touched in an unwanted way were found to be associated with depression. Conclusion and practical implications Implementing the HEEADSSS interviewing assessment within medical encounters with refugee adolescents is one efficient way to detect risky health behaviors and mental health problems. Interventions need to be implemented as early as possible in the refugees’ journey to help them cope and gain resilience. Training health care providers to conduct the questionnaire and delivering brief counseling when required is recommended. Establishing a network of referrals to provide multidisciplinary care to adolescents can be helpful. Obtaining a fund to distribute safety helmets for adolescent motorbike drivers can be a way to reduce injuries. More research among adolescent refugees in multiple settings, including teenagers in the host country, is needed to serve this population better.